2. Complete the following. a) Simplify \( \left(\frac{x}{2}-\frac{5}{x}\right)^{2} \). b) Calculate the value of \( \frac{x^{2}}{4}+\frac{25}{x^{2}} \), if \( \frac{x}{2}-\frac{5}{x}=3 \). 3. Complete the following. a) Simplify \( \left(\frac{x}{3}-\frac{6}{x}\right)^{2} \). b) Then evaluate \( \frac{x^{2}}{9}+\frac{36}{x^{2}} \), if \( \frac{x}{3}-\frac{6}{x}=1 \).
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To simplify \( \left(\frac{x}{2}-\frac{5}{x}\right)^{2} \): We start by expanding the square: \[ \left(\frac{x}{2}-\frac{5}{x}\right)^{2} = \left(\frac{x}{2}\right)^{2} - 2 \cdot \frac{x}{2} \cdot \frac{5}{x} + \left(-\frac{5}{x}\right)^{2} = \frac{x^{2}}{4} - 5 + \frac{25}{x^{2}}. \] So, the simplified form is: \[ \frac{x^{2}}{4} - 5 + \frac{25}{x^{2}}. \] Now to calculate \( \frac{x^{2}}{4}+\frac{25}{x^{2}} \), given \( \frac{x}{2}-\frac{5}{x}=3 \): From the given equation, rearranging gives: \[ \frac{x}{2} = 3 + \frac{5}{x}, \] Multiplying both sides by \( 2x \) results in: \[ x^{2} = 6x + 10 \Rightarrow x^{2} - 6x - 10 = 0. \] Using the quadratic formula: \[ x = \frac{6 \pm \sqrt{(-6)^{2} - 4(1)(-10)}}{2(1)} = \frac{6 \pm \sqrt{56}}{2} = 3 \pm \sqrt{14}. \] Now substitute \( x^{2} = 4(3 + \sqrt{14})(3 - \sqrt{14})\): Calculating, we find \( \frac{x^{2}}{4} + \frac{25}{x^{2}} = 6 + \frac{25}{10} = 6 + 2.5 = 8.5. \) --- To simplify \( \left(\frac{x}{3}-\frac{6}{x}\right)^{2} \): When expanding this expression, we get: \[ \left(\frac{x}{3}-\frac{6}{x}\right)^{2} = \left(\frac{x}{3}\right)^{2} - 2 \cdot \frac{x}{3} \cdot \frac{6}{x} + \left(-\frac{6}{x}\right)^{2} = \frac{x^{2}}{9} - 4 + \frac{36}{x^{2}}. \] Thus, the simplified expression is: \[ \frac{x^{2}}{9} - 4 + \frac{36}{x^{2}}. \] Next, to evaluate \( \frac{x^{2}}{9}+\frac{36}{x^{2}} \) when \( \frac{x}{3}-\frac{6}{x}=1 \): From the equation given, rearranging gives: \[ \frac{x}{3} = 1 + \frac{6}{x}. \] Multiplying through by \( 3x \) yields: \[ x^{2} = 3x + 18 \Rightarrow x^{2} - 3x - 18 = 0. \] Using the quadratic formula, we have: \[ x = \frac{3 \pm \sqrt{(3)^{2} + 4(18)}}{2} = \frac{3 \pm \sqrt{81}}{2} = \frac{3 \pm 9}{2}. \] Solving gives \( x = 6 \) or \( x = -3 \). Substituting \( x^{2} = 36 \), we find: \[ \frac{x^{2}}{9} + \frac{36}{x^{2}} = 4 + 1 = 5. \]